Developing Vocabulary Learning Cards with Islamic Contexts for Indonesian Muslim Young Learners - Hasibuan, Ahmad Sakti Alhamidi; Hasibuan, Kalayo; Zulhidah (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study explores the development of English word cards integrated with Islamic perspectives as vocabulary learning media for Muslim young learners in Indonesia. Using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—the research aims to provide culturally relevant materials that align with learners’ religious values. The resulting product consists of 26 double-sided alphabet-based cards featuring Islamic vocabulary, visual aids, and contextual Quranic references. Conducted in three Islamic elementary schools, the development process included needs analysis, expert validation, and trials involving students and teachers. Data were collected through questionnaires, interviews, observation, and pre-test/post-test instruments. Results showed significant improvement in vocabulary acquisition, student engagement, and learning motivation. Expert validation yielded an average score of 89%, and practicality assessment reached 80.6%. The paired sample t-test confirmed the effectiveness of the media. This research contributes to the integration of language instruction with character and faith development in Islamic educational settings.